Anti-Inflammatory and Antinociceptive Potential of Phytochemicals Derived from Urtica massaica: A Comprehensive Review - Ogare, James; Mwiti Kibiti, Cromwell; Piero Ngugi, Mathew; Onsongo Apiri, Benard; Mae Makonde, Huxley (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Urtica massaica, commonly known as the stinging nestle belonging to the family Urticaceae is used either as a vegetable or as food additive and as medicine in traditional African societies. It is a perennial herb that grows in wet parts of Kenya highlands and whose use in treating inflammation and pain among the natives in Kenya highlands has been common. Inflammation and pain management is still a problem in the treatment processes. The two medical indications have been regularly treated using non-narcotic drugs such as non-steroidal anti-inflammatory drugs, which have proved to cause adverse side effects. Therefore, there is need to use bioactive compounds from natural sources like Urtica massaica as an alternative treatment. This review focused on the phytochemicals derived from the plant species Urtica massaica, its anti-inflammatory and analgesic effects. The mechanisms by which the phytochemicals exert their anti-inflammatory and analgesic effect was also reviewed. Information on the safety and toxicity of Urtica massaica was also reviewed. The references reviewed were obtained from peer reviewed scientific journal articles. These articles were searched from databases including PubMed, Google Scholar (http: //scholar.google.com) and Science Direct (http://www.science direct.com). This review focused on data published from the year 2014 up to 2024. The findings obtained indicated that Urtica massaica has over 50 phytochemicals, flavanoid derivatives being the main anti-inflammatory and analgesic compound. However, there is need to isolate the bioactive compounds and further investigate the mechanisms by which they exhibit their anti-inflammatory and antinociceptive effect.